2021
DOI: 10.1155/2021/5927064
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanism of TL1A Expression on Epithelial-Mesenchymal Transition during Chronic Colitis-Related Intestinal Fibrosis

Abstract: Background and Aims. Recent evidences reveal that epithelial to mesenchymal transition (EMT) exacerbates the process of intestinal fibrosis. Tumor necrosis factor-like ligand 1A (TL1A) is a member of the tumor necrosis family (TNF), which can take part in the development of colonic inflammation and fibrosis by regulating immune response or inflammatory factors. The purpose of this study was to elucidate the possible contribution of TL1A in onset and progression of intestinal inflammation and fibrosis through E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
1
14
2
Order By: Relevance
“…Rs10114470 polymorphism is considered to be a loci for IBD susceptibility in Chinese Han population ( Table 2 ) ( 80 ). Furthermore, TL1A gene rs6478109 polymorphism is an independent factor of surgery, which affects the long-term efficacy of anti-TNF antibody therapy ( 72 ). Interestingly, anti-TL1A drug (PF-06480605) improved tissue inflammation and inhibited expression of fibrotic pathways, and reduced intestinal pathogens in UC patients ( 82 ).…”
Section: Association Between Tl1a and Inflammatory Autoimmune Diseasesmentioning
confidence: 99%
“…Rs10114470 polymorphism is considered to be a loci for IBD susceptibility in Chinese Han population ( Table 2 ) ( 80 ). Furthermore, TL1A gene rs6478109 polymorphism is an independent factor of surgery, which affects the long-term efficacy of anti-TNF antibody therapy ( 72 ). Interestingly, anti-TL1A drug (PF-06480605) improved tissue inflammation and inhibited expression of fibrotic pathways, and reduced intestinal pathogens in UC patients ( 82 ).…”
Section: Association Between Tl1a and Inflammatory Autoimmune Diseasesmentioning
confidence: 99%
“… 23 A study in 2021 found that the expression of TL1A in intestines of CD patients was almost twice as high as that in healthy individuals. 31 The expression of TL1A was negatively associated with E-cadherin expression, whereas positively associated with β-catenin and α-SMA expression, implying that TL1A might be involved in the process of epithelial-to-mesenchymal transition (EMT). 31 Indeed, evidence from both CD patients and a DSS-induced murine model indicated that TL1A could induce EMT through interleukin (IL)-13 and TGF-β1/Smad3 pathway [ Figure 2(c) ].…”
Section: Search Strategymentioning
confidence: 99%
“… 31 The expression of TL1A was negatively associated with E-cadherin expression, whereas positively associated with β-catenin and α-SMA expression, implying that TL1A might be involved in the process of epithelial-to-mesenchymal transition (EMT). 31 Indeed, evidence from both CD patients and a DSS-induced murine model indicated that TL1A could induce EMT through interleukin (IL)-13 and TGF-β1/Smad3 pathway [ Figure 2(c) ]. 31 Another interesting molecule AGR2 was identified via secretome profile of epithelium in ileal CD strictures.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that the abnormal expression of certain genes, such as nucleotide-binding oligomerization domain 2 (NOD2), toll-like receptors-4 (TLR4), and tumor necrosis factor-like ligand 1A (TL1A), might be related to the development of intestinal brosis 5, 7 . These genes play a role in intestinal brogenesis via regulating certain important processes, including epithelial-mesenchymal transition (EMT) initiation and progression, brogenic signal transduction, and macrophage-broblast program [7][8][9] . However, current studies have failed to identify the relationship between the dynamic uctuation of gene expression and colitis-related intestinal brosis.…”
Section: Introductionmentioning
confidence: 99%